ACCESS AND PERMANENCE IN THE EDUCATIONAL SYSTEM: FACTORS AFFECTING HIGH SCHOOL EDUCATION OF STUDENTS IN THE MUNICIPALITIES OF SARDINATA AND TIBÚ NORTE DE SANTANDER. - Andrés Michael Ordoñez Andrade; Tatiana Lucero Leal Pabón; Sonia Alejandra López (LÍNEA IMAGINARIA, 2025)
The article analyzes the impact on the improvement of access and retention conditions in the high school education system in the municipalities of Sardinata and Tibú, Norte de Santander. It presents the results of a citizen oversight conducted in rural educational institutions, focusing on components such as food strategies, teaching quality, and infrastructure. The oversight revealed gaps in the delivery of the School Feeding Program (PAE), lack of awareness about criteria for targeting beneficiaries, and inconsistencies in the quality of food. The study identified barriers to access, and retention associated with poverty, inadequate infrastructure and transportation, armed conflict, work responsibilities, and teenage pregnancy. Dropout arises from the dilemma of choosing between studying or working to contribute economically. Integrated policies across the educational, economic, and social sectors, coordinated at the municipal, departmental, and national levels, are needed to ensure the right to quality education under equitable conditions in these areas. The study provides recommendations and aims to serve as a roadmap for the participatory construction of inclusive educational policies in the region.